SUPERCONDUCTIVITY: THEORETICAL FOUNDATIONS, MECHANISMS AND MODERN APPLICATIONS (American Journal of Technology and Applied Sciences, 2025)
This article examines the physical nature of superconductivity, its microscopic mechanisms, and its applications in modern technologies. It highlights the historical discovery of superconductivity as well as its fundamental characteristics, such as zero electrical resistance and the Meissner effect. Within the framework of BCS theory, the formation of Cooper pairs and the emergence of an energy gap are discussed as key factors governing the transition of materials into the superconducting phase. Differences between type-I and type-II superconductors—including the roles of London penetration depth, coherence length, and Abrikosov vortices—are scientifically analyzed. The article also explores the properties of high-temperature superconductors and the contemporary hypotheses regarding their mechanisms. Additionally, the practical use of superconducting materials in MRI systems, quantum computers, magnetic levitation transport, and energy transmission technologies is reviewed. The study substantiates the fundamental significance of superconductivity and highlights its future scientific and technological potential.